(untitled) (Bangladesh Journal of Child Health, 2013)
Klippel-Trenaunay-weber syndrome is a rare congenital condition usually presenting with port wine stains, excessive growth of bones and soft tissue, and varicose veins. This occurs most commonly in the legs, but it also may affect the arms, face, head, or internal organs. We report a term male neonate presented with port wine stain, varicose veins and excessive growth of soft tissue of lower limbs consistent with Klippel-Trenaunay-Weber syndrome. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17271 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 130-132